Petrography and geochemistry of the enriched basaltic shergottite Northwest Africa 2975. (13th November 2015) - He, Qi; Xiao, Long; Balta, J. Brian; Baziotis, Ioannis P.; Hsu, Weibiao; Guan, Yunbin
Abstract: We present a study of the petrology and geochemistry of basaltic shergottite Northwest Africa 2975 (NWA 2975). NWA 2975 is a medium‐grained basalt with subophitic to granular texture. Electron microprobe (EMP) analyses show two distinct pyroxene compositional trends and patchy compositional zoning patterns distinct from those observed in other meteorites such as Shergotty or QUE 94201. As no bulk sample was available to us for whole rock measurements, we characterized the fusion crust and its variability by secondary ion mass spectrometer (SIMS) measurements and laser ablation inductively coupled plasma spectroscopy (LA‐ICP‐MS) analyses as a best‐available proxy for the bulk rock composition. The fusion crust major element composition is comparable to the bulk composition of other enriched basaltic shergottites, placing NWA 2975 within that sample group. The CI‐normalized REE (rare earth element) patterns are flat and also parallel to those of other enriched basaltic shergottites. Merrillite is the major REE carrier and has a flat REE pattern with slight depletion of Eu, parallel to REE patterns of merrillites from other basaltic shergottites. The oxidation state of NWA 2975 calculated from Fe‐Ti oxide pairs is NNO‐1.86, close to the QFM buffer. NWA 2975 represents a sample from the oxidized and enriched shergottite group, and our measurements and constraints on its origin are consistent with the hypothesis of two distinct Martian mantle reservoirs: a reduced, LREE‐depleted reservoir and an oxidized, LREE‐enriched reservoir. Stishovite, possibly seifertite, and dense SiO2 glass were also identified in the meteorite, allowing us to infer that NWA 2975 experienced a realistic shock pressure of 30 GPa.